Ectima gangrenoso: Relato de caso - Lastoria, Joel Carlos [UNESP]; Galli, Gustavo R. V.; Marques, Silvio Alencar [UNESP]; Costa, Adriana Dias; Fioretto, José Roberto [UNESP]; Bonatto, Rossano César [UNESP] (My University, 1996)
Report of a case of ecthyma gangrenosum with septicemia by Pseudomonas aeruginosa with favorable evolution in a 3-month-old boy. This disease is relatively rare, potentially lethal and the early diagnosis and treatment has an important role in the clinical evolution.
Ecthyma gangrenosum: Report of a case
Keywords: ecthyma; Pseudomonas aeruginosa; septicemia; amikacin; ampicillin; ceftriaxone; oxacillin; case report; human; human tissue; infant; male; pseudomonas aeruginosa